2009
DOI: 10.1002/jor.20750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovariectomy on bone turnover, porosity, and biomechanical properties in ovine compact bone 12 months postsurgery

Abstract: Compact bone makes up approximately 80% of the human skeleton by mass; but there are little data available on the effects of increased bone turnover on compact bone mechanical and material properties. This study addresses this question by measuring intracortical remodeling, resorption cavity number, and porosity in an ovariectomized (OVX) sheep model, and measures changes in biomechanical properties. Thirty-eight sheep were divided into two groups. Group 1 were controls (n ¼ 19), and Group 2 were ovariectomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 31 publications
6
43
0
1
Order By: Relevance
“…However, another study has showed that changes do not occur ubiquitously throughout the proximal femur [8]. In the current study the twelve month estrogen deficient group also showed reduced crystallinity indicative of the increased turnover, which is confirmed by the gene expression data presented and previous 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w 16 work on these animals [39]. In addition Figure 7 provides epifluorescence histological micrographs confirming the increased turnover in the ovariectomised group relative to the controls.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, another study has showed that changes do not occur ubiquitously throughout the proximal femur [8]. In the current study the twelve month estrogen deficient group also showed reduced crystallinity indicative of the increased turnover, which is confirmed by the gene expression data presented and previous 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w 16 work on these animals [39]. In addition Figure 7 provides epifluorescence histological micrographs confirming the increased turnover in the ovariectomised group relative to the controls.…”
Section: Discussionsupporting
confidence: 77%
“…High levels of bone turnover are visible after 12 months in (a) OVX bone while low levels are seen in (b) control bone. Histological data on these animals can be found in previous studies from our group [39,40]. 198x99mm (47 x 40 DPI) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 …”
Section: Discussionmentioning
confidence: 92%
“…These ovine studies also found that, as the animals progressed into long-term oestrogen deficiency, there was no significant difference in cortical compressive strength by 31 months post-OVX (Healy et al 2010;Kennedy et al 2009). …”
Section: Discussionmentioning
confidence: 75%
“…Ct.Th, Ct.Cs.Th, Ct.Ar, MMI(p), Ecc, BMD, BV, BV/TV, BS, BS/TV, Tb.Th, Tb.N, E.Con, E.Con.D and DA were severely decreased, while Ct.Pe.Pm, Ct.En.Pm, Ct.Po, TV, BS/BV, Tb.Sp, Tb.Pf and SMI were significantly increased in the OVX group compared to the sham group. These alterations provide evidence for increased osteoclastic activity due to estrogen deficiency [73] . It is known that estrogen can inhibit bone resorption and destruction by controlling the number and the activity of osteoclasts [74] .…”
Section: Effects On Bone Histopathologymentioning
confidence: 86%